2018
DOI: 10.1101/385872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing Aedes albopictus breeding sites through education: a study in urban area

Abstract: Aedes albopictus tends to proliferate in small, often man-made bodies of water, largely present in urban private areas. For this reason, education and community participation are considered crucial for source reduction and mosquito control. In the current study, we tried to relate for the first time in Greece, the effectiveness of resident education in an urban area with the number of breeding sites based on previous KAP (knowledge, attitudes and practices) studies. Our study examines the relationship between … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Also, the attachment of eggs to the tires is important for the protection of Aedes population during the mosquito off season. However, the results showed that both species have the capacity to adapt to different breeding habitats such as discarded tanks, flower pots and water bottles, which is similar to reports of mosquito habits observed in other countries (Eritja et al, 2005;Seidahmed & Eltahir, 2016;Mathias et al, 2017;Stefopoulou et al, 2018). In this present study, tire dumps and used tires were mainly targeted for sampling to increase the possibility that immature stages of the species would be found.…”
Section: Discussionsupporting
confidence: 85%
“…Also, the attachment of eggs to the tires is important for the protection of Aedes population during the mosquito off season. However, the results showed that both species have the capacity to adapt to different breeding habitats such as discarded tanks, flower pots and water bottles, which is similar to reports of mosquito habits observed in other countries (Eritja et al, 2005;Seidahmed & Eltahir, 2016;Mathias et al, 2017;Stefopoulou et al, 2018). In this present study, tire dumps and used tires were mainly targeted for sampling to increase the possibility that immature stages of the species would be found.…”
Section: Discussionsupporting
confidence: 85%
“…However, these studies also showed that a significant proportion of the surveyed persons had only a partial knowledge of the type of containers used as breeding sites, or identified other locations that are not suitable as breeding sites (15,(18)(19)(20)(21)(22)(23). For instance, in Lyon, 81.6% of the respondents believed that tiger mosquitoes breed in vegetation that in fact is suitable resting sites for adults, but cannot serve for larval development (18).…”
Section: Knowledge Of Larval Breeding Sites and Mbidsmentioning
confidence: 99%
“…For instance, in Lyon, 81.6% of the respondents believed that tiger mosquitoes breed in vegetation that in fact is suitable resting sites for adults, but cannot serve for larval development (18). Morse et al (15) showed that empty containers or rain gutters were not associated with potential breeding sites even though they represent highly suitable larval habitats for In Greece, a minority of respondents was able to identify correctly the place were mosquitoes lay their eggs and larvae grow (20,22,23). Similar observations were made from a German study where only 11.6% of respondents identified tree holes as potential water-holding larval habitats in their gardens (19).…”
Section: Knowledge Of Larval Breeding Sites and Mbidsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the species breeds in small containers (Stefopoulou et al, 2018), the water temperature can quickly reach high values, even if the air temperature is lower (Kumar et al, 2018). During spring, the temperature conditions often allow a complete development from egg to adult in 2-3 weeks; however, clear field information on the mean duration of a generation time is still missing.…”
Section: Articlementioning
confidence: 99%